Associations of discharge destination and length of stay in lower extremity free flap reconstruction. Issue 1 (28th February 2023) - Donato, Daniel; Veith, Jacob; Holoyda, Kathleen; Magno-Padron, David; Simpson, Andrew; King, Brody; Agarwal, Jayant
Abstract: Patients with lower extremity defects requiring free flap reconstruction often have difficult postoperative courses with prolonged length of stay and need for transfer to a post-acute care facility. The primary aim of this study was to determine associations of preoperative and perioperative variables with length of stay and discharge destination in patients undergoing lower extremity free flap reconstruction. The secondary aim was to determine associations of various complications with their discharge destination. The 2011– 2017 NSQIP database was queried for CPT codes for free flap procedures and ICD-9/ICD-10 codes for lower extremities. Univariate and multivariate analyses were used to determine associations of preoperative and perioperative variables with length of stay and discharge destination in patients undergoing lower extremity free flap reconstruction and associations of complications with their discharge destination. A total of 420 patients were identified who underwent lower extremity reconstruction in 2011–2017. Of 79.8% were discharged home and 21.2% were discharged to destinations other than home. On multivariate analysis, female gender, age > 55, ASA class > 2 and dependent functional status were found to have independent associations with discharge to post-acute care facilities. ASA classification greater than 2, active smoking, and discharge to a post-acute care facility all were independently associated with prolonged length of stay. Increased length of stay and discharge to post-acute care facility are closely associated. Understanding variables that influence length of stay and need for discharge to post-acute care facilities can help identify patients that may be triaged through appropriate interventions and expectation management.